An examination and evaluation of multi-level governance during migration crisis - Rijavec, Danila (Central European Public Administration Review, 2018)
Paper presents the value added to the analysis of the functioning of multi-level governance in the context of EU. Furthermore, it contributes to the small state studies, as the mitigation of crisis from the perspective of small state is analysed. The aim of the research was to determine whether the multi-level governance during the large-scale crisis was successful and what factors affected the level of success. The analysis utilizes of the case study method, where the crisis responses during the peak of Western Balkan migration route and Slovenia as a small state on Schengen border serve as examples of examination and evaluation. Results show unsuccessfulness of multi-level governance during the crisis, with mostly top-down direction of decision-making, and particularly the subnational level being poorly involved into the process. In addition, also layering of policy creation and implementation can be observed. The results of the analysis also pointed out that the multi-level governance in the case of migration crisis on the Western Balkans Route can be positioned as the type 1 governance, if we follow the outline of Hooghe and Marks (2003). The results indicate that unsuccessful multi-level governance had negative impacts on managing the crisis, as well as on perceptions about EU and Schengen Zone. This study is novel in its content, as it represents the first examination and evaluation of multi-level governance during the EU migration crisis, where Western Balkan route and Slovenia as small state on the outer Schengen zone border serve as a case study for the evaluation.
Keywords: Evropska unija; krizni management; migracije; migracijska politika; migrantska kriza; Slovenija; večnivojsko upravljanje